Comparative transcriptional analysis for Toll-like receptors, inflammatory cytokines, and apoptotic genes in response to different cytolethal-encoding and noncoding isolates of Salmonella enterica and Campylobacter jejuni from food and human stool. (August 2019) - Ganji, Leila; Alebouyeh, Masoud; Shirazi, Mohammad Hassan; Zali, Mohammad Reza
Abstract: Diversity of Campylobacter and Salmonella strains in interaction with epithelial cells may explain distinct modes of the pathogenesis, varying from mild watery to severe inflammatory diarrhea. We analyzed impact of this diversity, in relation to carriage and expression of cytholethal distending toxin B ( cdtB ), on alteration of IL-8, TNF-α, TLR2, TLR4, TLR5, CASP3 mRNA and cytokine levels in HT-29 cell line. A diversity was observed for induction of genes among different strains. Great diversity in IL-8 induction was detected between cdt B + and cdt B − strains. Early analysis showed down-regulation of TNF-α, mostly among cdtB + strains. Any increase or decrease in expression of TLR2 in the cdtB − C. jejuni strains was orderly correlated with increase or decrease of TLR4 and TNF-α . Up-regulation of CASP3 was followed by upregulation of TLR2, -4 and/or TNF-α, regardless to the cdtB status. In conclusion, induction of inflammatory response could mediate by distinct C. jejuni and S. enterica strains by several ways. Highlights: Strains of Campylobacter and Salmonella interact with the intestinal cells in different ways. A greater colonization rate occur in CdtB-encoding vs non-coding strains of Salmonella enterica . IL-8 can induce greatly in C. jejuni and S. enterica strains expressing CdtB at higher level. TLR4, TLR2, and TNF-α are cooperatively involved in immune response against these pathogens.